ANALISIS TNGKAT KESEHATAN BANK SEBELUM DAN SETELAH MERGER PADA PD.BPR BKK KARANGMALANG KABUPATEN SRAGEN - Edi Wibowo, Suparno & (Universitas Slamet Riyadi, 2009)
ABSTRACT This research aim to to know the storey;level of significance difference mount the bank health of before and after merger of at finance ratio : (1) capital Sufficiency (Capital Adequasy Ratio), (2) Quality Of Productive Asset (KAP), (3) Productive Asset Abolition Exclusion (PPAP), (3) Loan to Deposit Ratio (LDR) of at PD. BPR BKK Karangmalang of Sub-Province Sragen. Date for the comparison of is health storey; level of before merger that is year 2005 and mount the health after merger that is year 2007. Technique analyse to use the different test two mean.Result of analysis obtained (1) Difference of ratio of Capital Adequasy Ratio (CAR) mount the significance of equal to 0,000 < 0,05, so that Ho refused so that first hypothesis that there is difference of significance of ratio CAR of before and after merger proven. (2) Difference of ratio KAP mount the significance 0,00 < 0,05 so that both/ second hypothesis supported by result of this research. (3) different Test of ratio PPAP mount the significance of equal to 0,000 < 0,05 so that hypothesis raised to be supported by this research result. (4) different Test of ratio ROA mount the significance of equal to 0,000 < 0,05 so that hypothesis raised to be supported by this research result. (5) different Test of ratio BOPO mount the significance of equal to 0,001 < 0,05 so that hypothesis raised proven. ( 6) different Test of ratio of Cash Ratio mount the significance of equal to 0,000 < 0,05 so that hypothesis proven. (7) different Test of ratio LDR mount the significance of equal to 0,000 < 0,05 so that hypothesis raised to be supported by this research result. Keywords : CAR, KAP, PPAP, ROA, BOPO, Cash Ratio, LDR